THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDE WITH VULVA HYGIENE BEHAVIOUR ON FEMALE STUDENTS WITH MENSTRUATION AT JUNIOR HIGH SCHOOL 14 SOUTH TANGERANG - Handayani, Lili; Haque, Bunga Romadhona (HEARTY, 2024)
Background : Teenagers are individuals with an age range of 10-19 years. The adolescents are going through a transition period from childhood to adulthood. Knowledge about hygiene during menstruation among adolescents tends to be inadequate. Some adolescents know the good and correct way for personal hygiene during menstruation, when to change pads, and how to wash pads. Behavior that lacks hygiene during menstruation will have a negative impact and cause the spread of fungal and bacterial infections.Objective : To determine the relationship between knowledge and attitude with vulva hygiene behavior during menstruation in female adolescents at SMPN 14 South Tangerang City. Methods : The research conducted was quantitative research using an analytic design. This study used a cross sectional method. Total sample needed for this research is 35 people. Results : Of 35 respondents who had good knowledge, the majority had good vulvar hygiene behavior during menstruation, which is 29 respondents (96.7%) while 5 respondents who had poor knowledge mostly had poor vulvar hygiene behavior during menstruation, which is 3 respondents (3.3%). The chi square statistical test results showed a correlation between young women’s knowledge and attitudes and their implementation of vulva hygiene. Conclusions and Suggestions: The behavior of adolescent girls during menstruation obtained the results that all adolescent girls at SMPN 14 South Tangerang City have a good behavior category, namely 31 students (88.6%) while adolescent girls who have sufficient behavior are 4 students (11.4%). This research is expected to be a means of information and learning for students to increase understanding of vulva hygiene.